FAKTOR YANG BERHUBUNGAN DENGAN INTENSITAS KEKAMBUHAN HIPERTENSI PADA LANSIA DI POSYANDU ALAMANDA PANTI KABUPATEN JEMBER - Sujud Priono; Kustin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
Hypertension can recur because hypertension cannot be cured, but can be controlled and can reduce the risk of recurrence by improving lifestyle. Based on preliminary studies found the problem of elderly knowledge about coping stress, coping ability of stress and the intensity of hypertension recurrence. The purpose of this study is to analyze factors related to hypertension recurrence intensity. The study design uses correlation analytic with cross sectional approach. The study population was 65 respondents, with a large sample of 56 respondents taken by simple random sampling. How to collect data using documentation and questionnaires. Data analysis techniques using the Rank Spearman test. The results showed that the p-value (0.844) <α (0.05) means that there is a relationship of knowledge with stress coping in the elderly at the Posyandu Alamanda Panti Jember and p-value (-0.417) <α (0.05) means that there is a stress coping relationship with the intensity of hypertension recurrence in the elderly at Posyandu Alamanda Panti Jember. Midwives are expected to provide counseling related to knowledge and skills about stress coping in the elderly